Overcoming the carbon trap: Climate policy and technology tipping - Lucas Bretschger; Evgenij Komarov; Matthias Leuthard (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
We construct an overlapping generations model in which the choice between dirty and clean technology hinges on the economy's capital stock, susceptible to climate-induced depreciation. The process of capital accumulation contributes to environmental emissions, yet their intensity can be mitigated through a shift to cleaner production methods. The tipping point of technological transition is endogenously determined, leading to a diverse range of potential long-term outcomes shaped by capital endowment, pollution intensity, climate vulnerability, and clean factor productivity. Our analysis reveals the possibility of an economy converging into a "carbon trap", characterized by a sustained equilibrium marked by elevated pollution and diminished income, despite the feasibility of pursuing green growth. Additionally, we present optimal policy measures and simulations that highlight the temporal disparities between the socially optimal timing for transitioning to green technology and the timing dictated by market forces. Finally, to account for the high upfront costs of starting clean production, we extend the model by including a non-convexity in the production structure of the clean technology.
Keywords: 330; Carbon trap; technology tipping; climate damages; climate policy